Proof and Evidence in Cases Involving Compensation for Damage Caused to Health or Life of a Citizen as a Result of the Use of Drugs for Medical Use - SVIRIN, Yury A.; MOKHOV, Alexandr A.; GUREEV, Vladimir A.; ANDROSOVA, Irina G.; SHESTOV, Sergey N.; SHILOVSKAYA, Anna L. (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
The relevance of the investigated problem is caused by the ambiguous, contradictory jurisprudence in cases involving compensation for damage caused to health or life due to the use of drugs. In this connection, there arose a need of analysis of both the evidence examined by the court in resolving the above-mentioned categories of cases, and the proof process itself. This article aims to identify and disclose the general laws in proving the damage caused by drugs. This paper examines the evidence used in civil proceedings for compensation for damage caused by drugs; the necessity of securing of evidentiary presumption of guilt of a medical organization or manufacturer of medicines in the law; it also argues the duty of a medical institution or drug manufacturer to prove malice of the patient with caused bodily harm.